PENGEMBANGAN INDUSTRI BATIK SKALA KECIL DI KABUPATEN DAN KOTA PEKALONGAN DENGAN PENDEKATAN ANALYSIS HIERACHY PROCESS (AHP) - Sudantoko, Djoko (PRESTASI, 2010)
The main objective of the study is to develop small-scale batik enterprises in Pekalongan, Central Java-Indonesia. There were 15 key-persons had been carried out with in-depth interview who competents with the batik industriesâ activities. The analysis of Hierarchy Process (AHP) was employed to provide the empirical evidence of the developed strategy as prioritized by the study. The result on the analysis using AHP reveals the main priorities that need to be implemented in developing small sized batik industries are (1) open market opportunities (2) have training program to socialize entrepreneurship, and (3) provide trading and marketing centre for small sized business.Key-words: Small-scale, Enterprises, Batik, Analysis Hierarchy Process, AHP, Pekalongan